A cross-talk between DNA methylation and H3 lysine 9 dimethylation at the KvDMR1 region controls the induction of Cdkn1c in muscle cells. Issue 11 (1st November 2016) - Andresini, Oriella; Ciotti, Agnese; Rossi, Marianna N.; Battistelli, Cecilia; Carbone, Mariarosaria; Maione, Rossella
ABSTRACT: The cdk inhibitor p57 kip2, encoded by the Cdkn1c gene, plays a critical role in mammalian development and in the differentiation of several tissues. Cdkn1c protein levels are carefully regulated via imprinting and other epigenetic mechanisms affecting both the promoter and distant regulatory elements, which restrict its expression to particular developmental phases or specific cell types. Inappropriate activation of these regulatory mechanisms leads to Cdkn1c silencing, causing growth disorders and cancer. We have previously reported that, in skeletal muscle cells, induction of Cdkn1c expression requires the binding of the bHLH myogenic factor MyoD to a long-distance regulatory element within the imprinting control region KvDMR1. Interestingly, MyoD binding to KvDMR1 is prevented in myogenic cell types refractory to the induction of Cdkn1c . In the present work, we took advantage of this model system to investigate the epigenetic determinants of the differential interaction of MyoD with KvDMR1. We show that treatment with the DNA demethylating agent 5-azacytidine restores the binding of MyoD to KvDMR1 in cells unresponsive to Cdkn1c induction. This, in turn, promotes the release of a repressive chromatin loop between KvDMR1 and Cdkn1c promoter and, thus, the upregulation of the gene. Analysis of the chromatin status of Cdkn1c promoter and KvDMR1 in unresponsive compared to responsive cell types showed that their differential responsiveness to the MyoD-dependent induction of the gene does not involve just their methylation status but, rather, the differential H3 lysine 9 dimethylation at KvDMR1. Finally, we report that the same histone modification also marks the KvDMR1 region of human cancer cells in which Cdkn1c is silenced. On the basis of these results, we suggest that the epigenetic status of KvDMR1 represents a critical determinant of the cell type-restricted expression of Cdkn1c and, possibly, of its aberrant silencing in some pathological conditions.